Sex identification of the extant mega mammal, the lowland tapir, Tapirus terrestris (Tapiridae, Mammalia), by means of molecular markers: new outlook for non-invasive samples - Pelizzon, Cristiane [UNESP]; da Silva Carvalho, Carolina [UNESP]; Caballero, Susana; Galetti Junior, Pedro Manoel; Sanches, Alexandra (Springer Nature, 2017)
The knowledge of the sex ratio of threatened populations or species is pivotal since sub-optimal sex ratios can affect negatively the population growth and resilience. The vulnerable species, Tapirus terrestris, is rarely studied through traditional field methods and non-invasive genetic analyses have been employed using feces as source of DNA. Here, we evaluated two molecular markers for sex identification of tapirs. Amelogenin gene (AMEL) which is shorter in the Y chromosome (−20pb), failed in the determination of the sex of tapirs, even after the design of specific primers for the species. SRY marker, co-amplified with zinc-finger gene (ZF), had successful produced the sex identity for blood and scat samples. From a total of 45 feaces, 29 had the sex identified after three PCRS (64.4 %). In this way, these molecular markers are reliable tools for sex ratio determination using non-invasive samples of natural populations of this tapirs.
Keywords: Amelogenin; Sexing; SRY; Tapir; ZFX/ZFY